1976
DOI: 10.1093/cvr/10.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Augmented right ventricular function in systemic hypertension-induced hypertrophy

Abstract: The contractile properties of right ventricular papillary muscles from the hearts of 15 rats which had developed hypertension 6 weeks following renal artery ligation were compared with those from 14 normal litter-mates. In the experimental group, the heart weight-body weight ratio was increased by 39%, while the right ventricular weight-body weight ratio increased 20%. Right ventricular papillary muscles from the hypertensive rats demonstrated increased tension development at the apex of the length-active tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In agreement with these observations are the findings in the hemodynamically stressed left ventricle and nonstressed right ventricle in experimental systemic hypertension (Pool et al, 1976). In other studies of the nonstressed right ventricle in hearts with a hypertrophied pressureoverloaded left ventricle, the inotropic state of right ventricular papillary muscle was elevated (Pool et al, 1976). Moreover, investigations recently carried out in our laboratories on pulmonary artery-or aortic-banded dogs demonstrated similar temporal alterations between the two ventricles.…”
Section: Progression Of Myocardial Hypertrophysupporting
confidence: 80%
See 2 more Smart Citations
“…In agreement with these observations are the findings in the hemodynamically stressed left ventricle and nonstressed right ventricle in experimental systemic hypertension (Pool et al, 1976). In other studies of the nonstressed right ventricle in hearts with a hypertrophied pressureoverloaded left ventricle, the inotropic state of right ventricular papillary muscle was elevated (Pool et al, 1976). Moreover, investigations recently carried out in our laboratories on pulmonary artery-or aortic-banded dogs demonstrated similar temporal alterations between the two ventricles.…”
Section: Progression Of Myocardial Hypertrophysupporting
confidence: 80%
“…Thus, it appears that sustained, moderate ventricular outflow obstruction may lead to pathological hypertrophy. In agreement with these observations are the findings in the hemodynamically stressed left ventricle and nonstressed right ventricle in experimental systemic hypertension (Pool et al, 1976). In other studies of the nonstressed right ventricle in hearts with a hypertrophied pressureoverloaded left ventricle, the inotropic state of right ventricular papillary muscle was elevated (Pool et al, 1976).…”
Section: Progression Of Myocardial Hypertrophysupporting
confidence: 73%
See 1 more Smart Citation
“…We did not measure right ventricular or pulmonary arterial pressure. However, several investigators have reported an association between right and left ventricular hypertrophy (11,27,28), with some suggesting a hypertensive relation between the systemic and pulmonary vascular beds (2) and others stating the right ventricular hypertrophy in left ventricular pressure overload was independent of right ventricular hypertension (16).…”
Section: Discussionmentioning
confidence: 99%
“…These echocardiographic findings are in keeping with previous reports in experimental animals about the pathophysiology of inter-ventricular interaction. Left ventricular pressure overload induced by proximal aorta banding in experimental animals was found to be associated with increased biochemical and haemodynamic function of the 'nonstressed' ventricle as well as with development of biventricular hypertrophy [30]. Furthermore, banding of the dog pulmonary artery, in addition to causing right ventricular wall thickening, resulted in increased left ventricular mass and stiffness [31].…”
Section: Hypertensive Right Ventricular Hypertrophymentioning
confidence: 99%